Unreal for mobile and standalone VR : create professional VR apps without coding - Hillmann, Cornel (Apress, 2019)
Apply the techniques needed to build VR applications for mobile and standalone head-mounted displays (HMDs) using the Unreal Engine. This book covers the entire VR ecosystem including production tools, Unreal engine, workflows, performance and optimization, and presents two fully-developed projects to reinforce what you've learned. Media designers, CG artists and other creatives will be able to take advantage of real-time engine techniques and easy-to-learn visual scripting logic to turn their creations into immersive and interactive VR worlds. Gear VR, the Oculus Go and other Android based VR HMDs are becoming exciting new platforms for immersive business presentations, entertainment and educational solutions. The Unreal engine, one of the world's most powerful and popular game engines, is now free to use and has become increasingly popular for real-time visualizations and enterprise solutions in recent years. With Unreal's powerful blueprint visual scripting system, non-coders can now design blueprints in Unreal, unlock the power of rapid prototyping, and create complex interactions without a line of code. Get your copy of Unreal for Mobile and Standalone VR today and begin using this powerful tool-set to create high-end VR apps for a wide range of applications from games, B2B, to education. What You'll LearnExplore the VR ecosystem, including history, recent trends and future outlookReview tool set, graphics and animation pipeline (Blender, Zbrush, Substance Painter and others)Examine graphics optimization techniquesSet up a project and the target platformDesign interaction with Unreal blueprintsDeployments, testing, further optimizationWho This Book Is ForMultimedia designers, CG artists, producers, app developers. No coding experience is required.